Evaluation of additional electricity losses in electric networks using a meter - Allaev Kakhramon Rakhimovich; Adeel Saleem; Kholiddinov Ilkhombek Khosiljonovich; Atif Iqbal; Eraliev Khojiakbar Abdinabi ugli (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
In this article, additional electricity losses are calculated using the voltage imbalance factor. There is also a method for predicting extra losses in the case of longitudinal and transverse asymmetry, as well as information on how to measure power quality indicators. It is suggested that home appliances be used to monitor a separate power system's power quality indicators. The findings of investigations on the condition of asymmetry conducted in operational low voltage electrical networks are presented, along with an illustration of how to calculate additional electricity losses in low-voltage networks. In this article for this purpose, the author developed a Malika device, which is fully capable to measure, store, analyze, and draw conclusions from the results of all electrical quality indicators.